Governing insecurity in Japan the domestic discourse and policy response - Vosse, Wilhelm; Drifte, Reinhard; Blechinger-Talcott, Verena 1966- (London Routledge, Taylor & Francis Group, 2014)
"Since the end of the Cold War, Japan's security environment has changed significantly. On the global stage, while the United States is still Japan's most important security partner, the nature of the partnership has changed as a result of shifting demands from the United States, new international challenges such as the North Korean nuclear program and the rise of China. Moreover, Japan has been confronted with new, 'non-traditional' security threats such as international terrorism, the spread of infectious diseases, and global environmental threats. On the domestic level, demographic change, neo-liberal economic reforms and globalization all pose a challenge to the sustainability of the current Japanese lifestyle and have led to a heightened sense of insecurity among many Japanese. Focusing on the domestic Japanese discourse on security, this book expands the standard discussions on security that mostly focus on military security and security in international relations to include perspectives from domestic security, economic and livelihood security as well as sociological discussions of risk and risk management. The chapters cover issues such as Japan's growing perception of regional and global insecurity, the changing role of military force; the perceived risk of Chinese foreign investment; societal, cultural and labour insecurity and how it is affected by demographic changes and migration; as well as food insecurity and its challenges on health and public policy. In turn, each chapter asks how the Japanese public perceives these insecurities; how these perceptions influence the public discourse; who the main stakeholders of this discourse are; and how this affects state-society relations and decision on government policy in Japan. Governing Insecurity in Japan provides new insights into Japanese and international discourses on security, as well as the ways in which security is conceptualized in Japan. As such, it will be of huge interest to students and scholars working on Japanese politics, security studies and international relations."
Introduction / Wilhelm Vosse, Reinhard Drifte, Verena Blechinger-Talcott -- Threat perception and Japan's anti-militarism / Wilhelm Vosse -- Threats foreign and domestic : how the Japanese public balances between the two / Paul Midford -- Friend and foe : juxtaposing Japan's migration discourses / Gabriele Vogt --Can tabukayosei be a public philosophy of integration? : a political-theoretical perspective on immigration and security in Japan / Takashi Kibe -- Securitizing food in Japan : global crises, domestic problems and a neoliberal state / Hiroko Takeda -- Indispensable future workforce or internal security threat? : Securing Japan's future and immigration / David Chiavacci -- Feelings of insecurity : Japanese reactions to Chinese investments in Japan / Reinhard Drifte -- Effective for peace? : JSDF peacekeeping operations since 1992 / Garren Mulloy.
Includes bibliographical references and index.
Keywords: National security -- Social aspects -- Japan; National security -- Economic aspects -- Japan; National security -- Japan -- Public opinion; Human security -- Japan; Social psychology -- Japan